Flexibility profiles of European companies European Company Survey 2009 - Kerkhofs, Marcel; Ester, Peter; Roman, Amelia; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2010)
The flexibility practices of European companies were the subject of the European Company Survey (ECS) conducted by Eurofound in 2009. Managers and, where available, employee representatives in 27,000 companies were interviewed to establish what kind of flexibility measures were in place and how they were used. The results showed that the most common type of flexibility in companies across the EU Member States, Croatia, the former Yugoslav Republic of Macedonia and Turkey is working time flexibility.What became apparent is that flexibility measures are not used in isolation but are combined in packages. The aims and objectives behind the use of these clusters of practices diverge as well. In this report, a typology is developed which allows distinguishing between five flexibility profiles - differing in extent as well as focus. The report goes on to examine how the five profiles are linked to certain company characteristics and to company performance.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Flextime -- European Union countries; Industrial relations -- European Union countries; Labor market -- Europe; Electronic books